Ethical issues in political news translation in Kazakhstan - Inamzhanova, D. (M. Narikbayev KAZGUU University School of Liberal Arts, 2023)
This research aims to explore ethical issues in political news translation in Kazakhstan. Translation ethics is an integral part of quality translation. Its standard rules are well- described in translators’ codes of ethics. However, in the field of political news translation, the issues of ethics are often nuanced and do not adhere to the standard. This thesis critically analyses the existing literature on translation ethics and political news translation. The methodology involves semi-structured interviews with translators working in the field of political news. The purpose of this qualitative study is to identify the ethical challenges faced by translators in Kazakhstan and the strategies they use to minimize potential ethical dilemmas. Accuracy, confidentiality, transparency, and bias were identified as major attributes of ethical challenges in political news translation. It was also found that in order to avoid ethical challenges, translators in Kazakhstan should be familiar with the translator's code of ethics, organize and attend specialized training in political news translation, and combine theory and practice to produce high-quality translations. The results show that this industry needs to grow in Kazakhstan and that it is important to create programs to train political news translators based on key ethical principles. The study also provides implications for theory and practice
Keywords: translation ethics, the code of ethics, peculiarities of political news translation, ethical challenges, ways to minimize ethical dilemmas